IMPACT OF SOCIAL MEDIA USE IN POLITICAL CAMPAIGNS ON VOTER AWARENESS AMONG FIRST-TIME VOTERS AT SMAN 15 GARUT IN ELECTORAL PARTICIPATION - Muhammad Ilham Fadilah Ilham (PT. Jurnal Center Indonesia Publisher, 2025)
The use of social media in political campaigns significantly impacts the political awareness of first-time voters at SMAN 15 Garut. Validity and reliability tests of the research instrument indicate that the questionnaire used is valid and reliable, allowing for accurate measurement of the desired concepts. Simple linear regression analysis reveals a positive relationship between the social media use variable (X) and the level of voter political awareness (Y), with social media explaining approximately 23.1% of the variation in voter awareness. Although significant, the influence of social media does not explain the entire variation in voter political awareness. Other factors outside the research variables also contribute, indicating the complexity in understanding the factors that influence the political awareness of first-time voters. Therefore, it is suggested to integrate social media use into better political campaign strategies, considering the characteristics of first-time voters. Increased digital access and knowledge also need to be strengthened so that first-time voters can participate more actively and effectively in the democratic process.